ANALISA PENYEBAB KEMACETAN TERHADAP ARUS LALU LINTAS JALAN LINTAS SUMATERA PANGKALAN BALAI - Sarwandy, M. Hijrah Agung; Royan, Noto (Universitas Muhammadiyah Palembang, 2023)
This study focuses on survey studies on the analysis of the causes of congestion on the km15-km18 road sections. To find out the analysis of the causes of congestion, road capacity, vehicle volume, level of service, determine resolution of problems, and analyze average daily traffic by conducting field surveys for seven days. This research was conducted in 1 research segment, namely: on the Sumatran crossroads at Pangkalan Balai Km15-km18